The Effectiveness of Pre-Mommy Applications to Improving Knowledge, Behavior, and Psychological Conditions in The Preconception Period Women of Reproductive Age - Yulizawati Yulizawati; Henni Fitria; Rafika Oktova; Ikhwan Arief (Women, Midwives and Midwifery, 2023)
Background: Preconception care is provided to minimize adverse risk factors in fetal growth and development. in preconception care important educational aspects before encouraging the need for mobile education. .Mobile applications can be used to provide more practical preconception education. Purpose: The aim of this study was to investigate whether providing education through Premommy applications is beneficial in improving the knowledge, behavior, and psychological well-being of women during the preconception period. Methods: This study is quantitative research with pre-experimental design, one group pre-test and post-test. The study was conducted at the Religious Affairs Office in Padang City with 50 participants. Results: Results show an increased percentage of respondents with high knowledge (22%), good preconception behavior (16%), and mild anxiety levels (16%) after the intervention. Analysis test with Wilcoxon obtained p-value <0.05. Conclusion: There was an influence of intervention using the Premommy application on the level of knowledge, behavior, and psychological conditions. Professionals are expected to improve quality in providing preconception education using applications.